1999
DOI: 10.1073/pnas.96.23.13415
|View full text |Cite
|
Sign up to set email alerts
|

Aminopeptidase A inhibitors as potential central antihypertensive agents

Abstract: Overactivity of the brain renin-angiotensin system (RAS) has been implicated in the development and maintenance of hypertension in several experimental models, such as spontaneously hypertensive rats and transgenic mice expressing both human renin and human angiotensinogen transgenes. We recently reported that, in the murine brain, angiotensin II ( brain ͉ renin-angiotensin system ͉ zinc metalloproteases ͉ mercapto inhibitors ͉ blood pressure

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
171
0
4

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 177 publications
(183 citation statements)
references
References 49 publications
6
171
0
4
Order By: Relevance
“…It was reported that aminopeptidase A plays a role in the regulation of blood pressure by regulating the renin-angiotensin system in the brain (21). P-LAP/oxytocinase, which is also designated as insulin-regulated aminopeptidase, was shown to be the angiotensin IV receptor and may play a role in the memory retention and retrieval (22).…”
mentioning
confidence: 99%
“…It was reported that aminopeptidase A plays a role in the regulation of blood pressure by regulating the renin-angiotensin system in the brain (21). P-LAP/oxytocinase, which is also designated as insulin-regulated aminopeptidase, was shown to be the angiotensin IV receptor and may play a role in the memory retention and retrieval (22).…”
mentioning
confidence: 99%
“…APA and other components of the brain renin-angiotensin system (4) have been identified in several brain nuclei involved in the control of body fluid homeostasis and cardiovascular functions. Studies with specific and selective APA inhibitors (5) have shown that, in vivo, APA converts brain angiotensin II to angiotensin III (6) and that brain angiotensin III exerts a tonic stimulatory action on the central control of blood pressure (7). Thus, the central administration of APA inhibitors results in a large decrease in arterial blood pressure in alert spontaneously hypertensive rats (7), suggesting that brain APA is a putative central therapeutic target for the treatment of hypertension (reviewed in Ref.…”
mentioning
confidence: 99%
“…It is thought that the active peptides angiotensin II, III, or IV may have roles within the brain in functions as diverse as the regulation of cardiovascular and fluid homeostasis (2,3,11,19,35,40,41,46), reproduction (15), thermoregulation (28), memory (49), cognition, emotional responses to stress and anxiety, cerebral blood flow regulation, and brain developmental processes (39). However, some studies have questioned whether angiotensin is a neuropeptide because of its very low abundance in brain (23) and have proposed that an alternative endogenous ligand may act on angiotensin receptors in the brain (6).…”
mentioning
confidence: 99%